Determinants of Digital Health Based Learning in Primary and Secondary Education: Path Analysis - Alfiyani, Lina; Kusparlina, Eny Pemilu; Mukhlisin, Latutik; Salima, Faritsatul Fatin (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to develop a digital health-based learning model and identify the direct and indirect factors influencing students' digital health literacy in elementary and secondary schools in Madiun City. Methodology: A cross-sectional design was employed with primary data collected from 120 elementary and secondary school students. Data analysis was conducted using SPSS software and path analysis. Validated and reliable structured questionnaires were used as research instruments. Main Findings: Digital literacy is directly influenced by skills (b = 3.11; 95% CI = 1.66–4.56; p < 0.001) and attitudes (b = 3.27; 95% CI = 1.79–4.74; p < 0.001). Skills indirectly affect digital literacy through teaching quality (b = 7.15); teaching quality indirectly affects digital literacy through school facilities (b = 1.67); and school facilities influence digital literacy through family support (b = 1.94), all statistically significant (p < 0.001). Novelty/Originality of this study: This study introduces an integrative approach to enhancing digital health literacy by mapping psychosocial and structural pathways in school settings. It advances existing knowledge by proposing a conceptual model for curriculum development focused on digital health education in early education levels.